Correction: Microelectrochemical cell arrays for whole-cell currents recording through ion channel proteins based on trans-electroporation approach. Issue 4 (19th December 2019) - Zheng, Tianyang; Baaken, Gerhard; Behrends, Jan C.; Rühe, Jürgen
Abstract : Correction for 'Microelectrochemical cell arrays for whole-cell currents recording through ion channel proteins based on trans -electroporation approach' by Tianyang Zheng, et al., Analyst, 2020, DOI: 10.1039/c9an01737b.